Revealing the forest hidden value : the case study of Eritrea - Araia, Mulugheta Ghebreslassie (Stellenbosch : University of Stellenbosch, 2006)
Thesis (MScFor (Forest and Wood Science))--University of Stellenbosch, 2005.